Cancer, atrial fibrillation, and stroke. Issue 155 (July 2017) - Fitzpatrick, Tess; Carrier, Marc; Le Gal, Grégoire
Abstract: Cancer patients appear to be at increased risk for atrial fibrillation. Although surgery and chemotherapy exacerbate this risk, this association is observed even in the absence of any cancer-specific treatment. The underlying mechanism of this is likely multifactorial, but systemic inflammation and autonomic dysregulation are hypothesized to play critical roles. Cancer and atrial fibrillation are both independent risk factors for ischemic stroke; however, it is not clear whether this translates to an increased risk of stroke in patients with both comorbidities. As such, commonly used risk stratification tools including the CHADS2 score currently do not take cancer into account as a variable and it is possible that stroke risk is underestimated in this population. There is a paucity of data regarding anticoagulant choice in cancer patients with atrial fibrillation. Vitamin K antagonists are often preferred over direct oral anticoagulants; however, this may be changing in the near future as new trials specific to this patient population emerge. Highlights: The prevalence of atrial fibrillation (AF) may be higher in cancer patients. Relative risk of stroke in cancer versus non-cancer AF patients is not known. Current AF risk stratification tools do not take cancer into account as a variable. Vitamin K antagonists remain the main therapeutic option in cancer patients.